2009
DOI: 10.1088/0031-9155/54/21/009
|View full text |Cite
|
Sign up to set email alerts
|

A novel forward projection-based metal artifact reduction method for flat-detector computed tomography

Abstract: Metallic implants generate streak-like artifacts in flat-detector computed tomography (FD-CT) reconstructed volumetric images. This study presents a novel method for reducing these disturbing artifacts by inserting discarded information into the original rawdata using a three-step correction procedure and working directly with each detector element. Computation times are minimized by completely implementing the correction process on graphics processing units (GPUs). First, the original volume is corrected usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 29 publications
(34 reference statements)
2
108
0
Order By: Relevance
“…These artifacts may be the secondary artifacts introduced by the correction scheme and may be the reason the imaging quality remained inferior to that of native images. 15,16 In our results, the types of metal objects and the coil lengths did not affect the results of the investigated MAR algorithm. In assessing subjective image quality, we demonstrated that the MAR software substantially improved the visibility of the metal object vicinity, in which image qualities were most severely degraded before correction.…”
Section: Discussionsupporting
confidence: 44%
“…These artifacts may be the secondary artifacts introduced by the correction scheme and may be the reason the imaging quality remained inferior to that of native images. 15,16 In our results, the types of metal objects and the coil lengths did not affect the results of the investigated MAR algorithm. In assessing subjective image quality, we demonstrated that the MAR software substantially improved the visibility of the metal object vicinity, in which image qualities were most severely degraded before correction.…”
Section: Discussionsupporting
confidence: 44%
“…Consequently, no absorption can be computed and severe artefacts are induced as these zero entries are backprojected into the volume. 30 …”
Section: Extinction Artefactsmentioning
confidence: 99%
“…The MAR prototype algorithm (Fig 1) investigated is a modification and extension of the procedure first published by Prell et al 4 The MAR reconstructions were performed on an off-line prototype research workstation (Siemens). The algorithm consists of several steps.…”
Section: Metal Artifacts Reduction Algorithmmentioning
confidence: 99%
“…One of the first interpolationbased MAR algorithms used a 1D linear interpolation for singlerow CT data, which is inadequate for FDCT data. 3 The MAR algorithm investigated in this work, developed by Siemens Healthcare Sector, is a modification and extension of a recently published MAR procedure by Prell et al 4 We present validation of the FDCT MAR prototype algorithm by using a phantom study and an objective critique by 7 clinicians.…”
mentioning
confidence: 99%